Responsible leadership, organizational ethical culture, strategic posture, and green innovation. Issue 7 (11th June 2023) - Akhtar, Muhammad Waheed; Garavan, Thomas; Javed, Muzhar; Huo, Chunhui; Junaid, Muhammad; Hussain, Khalid
ABSTRACT : Leaders in service organizations are increasingly challenged to demonstrate leadership underpinned with a strong sense of responsibility. To date, a few studies have empirically investigated the influence of responsible leadership on organizational outcomes such as innovation. Drawing on signaling theory, this study reports the findings of the relationship between RL and green innovation in service firms through the mediating role of organizational ethical culture. We also test the moderating effect of strategic posture on this relationship. Using a three-wave research design and data collected from employees (n = 168) in hospitality organizations, we found that RL positively influences green innovation. We found support for the mediating effect of organizational ethical culture and the moderating role of strategic posture on the direct effect of responsible leadership on green innovation such that this direct effect is stronger where there is a progressive strategic posture. We highlight both the theoretical and practical implications of our findings.